Discovery of epigenetic probes against the bromodomain family of proteins - Clark, P (2015)
Chemical probes are necessary for elucidating the biochemical roles of proteins. Bromodomains are protein-interaction modules found in a family of proteins implicated in the epigenetic regulation of transcription; however, the individual roles remain unknown for many bromodomain proteins, without potent and selective ligands available to assist in their study. From lead compounds, a structure-based drug discovery program was to be explored with the use of biophysical assays and appropriate chemical methods to expediate development of probes against a number of these proteins. A fragment lead against BRD4 was developed into PNZ5, a potent (KD 5 nM) BRD4 probe with a high ligand efficiency. Although enantioselective syntheses and the use of an alternative synthetic route were unsuccessful, PNZ5 showed cytotoxic activity against gastric cancer cell lines that had proved resilient to existing anticancer agents. Optimisation of a lead compound against BRD9 resulted in the development of LP99, the ﬁrst reported BRD7/9 probe, that was potent (BRD9 KD 99 nM, BRD7 KD 909 nM), selective amongst bromodomain proteins and active in cells. An enantioselective synthesis was performed using chiral organocatalyts and LP99 was used to identify a previously unknown role of BRD7/9 in the regulation of inﬂammatory processes. Research is ongoing to assess further biochemical roles of these proteins with LP99. Arising from a more potent lead against BRD9, a series of structurally related compounds were synthesised to explore SAR around this ligand, however no improvement on the affinity of the lead was realised. Finally, based on disclosed lead structures against PCAF, a series of compounds were synthesised to replicate their activity. A number of important binding interactions were assessed and a lead structure was identiﬁed (KD 1 μM). Development is ongoing to progress this lead into the ﬁrst reported PCAF probe.